Bulk segregant analysis-sequencing and RNA-Seq analyses reveal candidate genes associated with albino phenotype in Brassica napus - Ye, Shenhua; Yang, Jie; Huang, Yingying; Liu, Jie; Ma, Xiaowei; Zhao, Lun; Ma, Chaozhi; Tu, Jinxing; Shen, Jinxiong; Fu, Tingdong; Wen, Jing (Frontiers in Plant Science, 2022)
Inheritable albino mutants are excellent models for exploring the mechanism of chloroplast biogenesis and development. However, only a few non-lethal albino mutations have been reported to date in Brassica species. Here, we describe a resynthesized Brassica napus mutant, whose leaf, stem, and silique tissues showed an inheritable albino phenotype under field conditions after the bud stage but green phenotype in the greenhouse during the whole growing season, indicating that the albino phenotype depends on environmental conditions. Compared with the green leaves of the field-grown wild-type (GL) and greenhouse-grown mutant (WGL) plants, white leaves of the field-grown mutant (WL) showed significantly lower chlorophyll contents and structural defects in chloroplasts. Genetic analysis revealed that the albino phenotype of WL is recessive and is controlled by multiple genes. Bulk segregant analysis-sequencing (BSA-Seq) indicated that the candidate regions responsible for the albino phenotype spanned a total physical distance of approximately 49.68 Mb on chromosomes A03, A07, A08, C03, C04, C06, and C07. To gain insights into the molecular mechanisms that control chloroplast development in B. napus, we performed transcriptome (RNA-Seq) analysis of GL, WGL, and WL samples. GO and KEGG enrichment analyses suggested that differentially expressed genes (DEGs) associated with leaf color were significantly enriched in photosynthesis, ribosome biogenesis and chlorophyll metabolism. Further analysis indicated that DEGs involved in chloroplast development and chlorophyll metabolism were likely the main factors responsible for the albino phenotype in B. napus. A total of 59 DEGs were screened in the candidate regions, and four DEGs (BnaC03G0522600NO, BnaC07G0481600NO, BnaC07G0497800NO, and BnaA08G0016300NO) were identified as the most likely candidates responsible for the albino phenotype. Altogether, this study provides clues for elucidating the molecular mechanisms underlying chloroplast development in B. napus.